IKLAN LAYANAN MASYARAKAT TENTANG NOMOPHOBIA DENGAN TEKNIK MOTION GRAPHIC - Surya Agung Perdana; Zubaidah A Zubaidah A (Universitas Negeri Padang, 2020)
Nomophobia (No Mobile Phobia) is a form of phobia in the form of fear and anxiety that occurs if someone does not hold a phone or gadget for a short time, so that it can cause stress. This condition is not only afraid of losing the smartphone but also runs out of battery and does not get the network. Excessive use of smartphones will have a negative impact on physical and psychological health. To provide an awareness and knowledge effort for the public about the information on the danger of gadget or nomophobia dependence, it is necessary to make a media with the title